2004
DOI: 10.1007/s00251-004-0694-x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression, and characterization of fugu CD4, the first ectothermic animal CD4

Abstract: We have cloned and sequenced the first ectothermic animal CD4 gene from fugu, Takifugu rubripes, using a public database of the third draft sequence of the fugu genome. The fugu CD4 gene encodes a predicted protein of 463 amino acids containing four extracellular immunoglobulin (Ig)-like domains, a transmembrane region, and a cytoplasmic tail. Fugu CD4 shares low identity of about 15-20% with avian and mammalian CD4 proteins. Unlike avian and mammalian CD4, fugu CD4 lacks the Cys pair of the first Ig-like doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 43 publications
3
72
0
Order By: Relevance
“…TCR-γ, CD4 and CD8α are surface marker genes of epithelial γδT cells, Th and Tc cells. Expression of CD4 and CD8 genes are essential for cell-mediated immune response and the development of T lymphocytes (Suetake et al, 2004). Up-regulation of these lymphocytes-related gene expression indicated that overexpression of carp ProTα b and Tβ-l may induce the development of T lymphocytes, and ultimately enhance the cell mediated immune response.…”
Section: Discussionmentioning
confidence: 99%
“…TCR-γ, CD4 and CD8α are surface marker genes of epithelial γδT cells, Th and Tc cells. Expression of CD4 and CD8 genes are essential for cell-mediated immune response and the development of T lymphocytes (Suetake et al, 2004). Up-regulation of these lymphocytes-related gene expression indicated that overexpression of carp ProTα b and Tβ-l may induce the development of T lymphocytes, and ultimately enhance the cell mediated immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The genomic organization of the halibut CD4-2 gene shows a close relationship with CD4 and LAG-3 genes, as the first domain D1 was shown to be dispersed between two exons. This is a special feature seen in the CD4 and LAG-3 genes of higher vertebrates, and found in all the teleost CD4 genes characterized to date [3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the F 43 was conserved in halibut CD4-2 ( Figure 2), and not in the classical four-domain halibut CD4 [3]. The two-domain CD4 of fugu is also in the possession of a phenylalanine corresponding to human F 43 [4], giving the consensus FxxK in halibut, fugu, and human but not in other CD4 like genes [3][4][5][6][7][8][9][10]. Other features common in mammalian and fish CD4 Igdomains are the presence of cysteines for intra-chain disulfide bridging and a core tryptophan forming an essential structural triad thought to stabilize most Ig-domains [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dendritic cells (DCs), 4 monocytes/macrophages, and B cells have been identified as major professional APCs (1,2). These APCs capture and process Ags and then present the processed antigenic peptides upon MHC molecules to the T cells.…”
mentioning
confidence: 99%